Evaluation of the importance of critical minerals in China - Ren, Xiaojuan; Fan, Fengyan; Liu, Qunyi; Lv, Yan (Frontiers in Earth Science, 2025)
Critical minerals are the basic resources that support many strategic industries, and the importance of their safety and security cannot be overstated. In recent years, as geopolitical conflicts have intensified, higher demands have been placed on the stable supply of critical minerals. The United States and the European Union have strengthened their mechanisms for securing the supply of critical minerals through the establishment of mineral security partnerships. China, as a large resource consumer, has a long evaluation interval for critical minerals, which needs to be re-examined to guarantee a stable supply of important mineral resources. This study identifies 32 assessed minerals based on China’s list of strategic mineral resources, with reference to the lists of critical mineral resources of the United States and the European Union. These minerals are categorized into long-term balanced developmental minerals, national strategic advantage minerals, and national strategic scarce minerals. Then, a comprehensive evaluation of the relative importance of the three types of minerals was carried out using the linear weighted sum method. The results show that among the classified minerals, nickel, gold, potash, chromium, tungsten, arsenic, bismuth, lithium, zirconium, and hafnium are of greater significance, phosphorus, molybdenum, barite, niobium, and tantalum are of lesser importance. Nickel, chromium, lithium, zirconium, and hafnium have a high supply risk. Potash and gold have good economic importance and market prospects, respectively, while tungsten, arsenic, and bismuth have a strong influence. According to the evaluation results, the corresponding suggestions are put forward.